Long-Term Outcomes Following Conventionally Fractionated Stereotactic Boost for High-Grade Gliomas in Close Proximity to Critical Organs at Risk - Repka, Michael C.; Lei, Siyuan; Campbell, Lloyd; Suy, Simeng; Voyadzis, Jean-Marc; Kalhorn, Christopher; McGrail, Kevin; Jean, Walter; Subramaniam, Deepa S.; Lischalk, Jonathan W.; Collins, Sean P.; Collins, Brian T. (Frontiers in Oncology, 2018)
Purpose/Objective: High-grade glioma is the most common primary malignant tumor of the CNS, with death often resulting from uncontrollable intracranial disease. Radiation dose may be limited by the tolerance of critical structures, such as the brainstem and optic apparatus. In this report, long-term outcomes in patients treated with conventionally fractionated stereotactic boost for tumors in close proximity to critical structures are presented. Materials/Methods: Patients eligible for inclusion in this single institution retrospective review had a pathologically confirmed high-grade glioma status post surgical resection. Inclusion criteria required tumor location within one centimeter of a critical structure, including the optic chiasm, optic nerve, and brainstem. Radiation therapy consisted of external beam radiation followed by a conventionally fractionated stereotactic boost. Oncologic outcomes and toxicity were assessed. Results: Thirty patients eligible for study inclusion underwent resection of a high-grade glioma. The median initial adjuvant EBRT dose was 50 Gy with a median conventionally fractionated stereotactic boost of 10 Gy. All stereotactic treatments were given in 2 Gy daily fractions. Median follow-up time for the entire cohort was 38 months with a median overall survival of 45 months and five-year overall survival of 32.5%. The median freedom from local progression was 45 months, and the five-year freedom from local progression was 29.7%. Two cases of radiation retinopathy were identified following treatment. No patient experienced toxicity attributable to the optic chiasm, optic nerve, or brainstem and no grade 3+ radionecrosis was observed. Conclusions: Oncologic and toxicity outcomes in high-grade glioma patients with tumors in unfavorable locations treated with conventionally fractionated stereotactic boost are comparable to those reported in the literature. This treatment strategy is appropriate for those patients with resected high-grade glioma in close proximity to critical structures.